Konsep Mengalir pada Sirkulasi Kendaraan dalam Redesain Terminal Bus Tipe-A Surodakan Trenggalek - Inas Oktavia Putri; Siti Azizah; Wiwik Widyo Widjajanti (Institut Teknologi Adhi Tama Surabaya, 2022)
Trenggalek Regency has fulfilled the needs of its people in the field of land transportation in the form of the Surodakan Type-A Bus Station which serves short-distance routes (inter-districts), medium-distance (between cities within provinces), and far (between cities between provinces). At Surodakan Bus Station, there are problems in the form of opposite circulation and have not been neatly arranged so that the circulation of buses, public passenger cars, managers and visitors is still mixed so that it seems unsafe for users. To reduce this problem, the Surodakan Bus Station was redesigned by clarifying the circulation path to make it easier for users. With the use of the concept of flowing on the land structure of the Surodakan Bus Station, it is hoped that the creation of a clear circulation of vehicles using the flow of circulation can be the main forming element of the row of facilities at the terminal. The design theme used is Neo-vernacular Architecture while still paying attention to local culture so that Trenggalek culture is not lost, besides that it can still increase visitor interest.